Analisis Dampak Investasi Asing Langsung Terhadap Pembangunan Infrastruktur di Indonesia - Jufri Jacob; Abdul Hamid; Amir Buhang; Nurjanna Ladjin; Suwardi Zakaria (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
One of the most important developments is infrastructure development. However, to build an infrastructure, developing countries such as Indonesia must have a large enough capital supply to carry out its development. Indonesia as a developing country has limitations in providing capital. This study aims to determine the impact of direct investment on infrastructure development in Indonesia. Infrastructure development is considered one of the main keys to driving economic growth and public welfare. The method used in this study is regression. Using secondary data processed with the help of SPSS software. The results of the study indicate that direct foreign investment has a positive impact on infrastructure development in Indonesia. Foreign investors directly provide financial resources and technology, which can accelerate infrastructure development which is the basis for long-term economic growth.